2000
DOI: 10.1161/01.hyp.36.6.1018
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Increases Baroreceptor Gain Sensitivity in Normal and Hypertensive Rats

Abstract: Abstract-Exercise training attenuates arterial hypertension and increases baroreflex sensitivity in spontaneous hypertension. However, no information exists regarding the portion of the baroreflex arch in which this attenuation takes place. We tested the hypothesis that exercise training increases the afferent pathway sensitivity of baroreflex control in both normotensive and spontaneously hypertensive rats (SHR). Arterial pressure and whole-nerve activity of the aortic baroreceptor (multifiber preparation) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
99
3
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 33 publications
15
99
3
13
Order By: Relevance
“…35 Animal studies, however, have shown that both acute and chronic exercise did improve baroreflex sensitivity in both normal and hypertensive rats. 36,37 In the present study, CPBR control of forearm vascular resistance did not significantly improve following 4 weeks of cycle exercise. A possible explanation for this lack of change could be the short duration of the exercise program.…”
Section: Cardiopulmonary Baroreceptor (Cpbr) Sensitivitycontrasting
confidence: 51%
“…35 Animal studies, however, have shown that both acute and chronic exercise did improve baroreflex sensitivity in both normal and hypertensive rats. 36,37 In the present study, CPBR control of forearm vascular resistance did not significantly improve following 4 weeks of cycle exercise. A possible explanation for this lack of change could be the short duration of the exercise program.…”
Section: Cardiopulmonary Baroreceptor (Cpbr) Sensitivitycontrasting
confidence: 51%
“…Whereas baseline AP is unaltered after training, the controlling mechanisms are changed. There is evidence supporting the increase in baroreflex gain in trained subjects (6,7,(9)(10)(11)23,29). Exercise training of normotensive male rats enhanced hypotension-induced tachycardia, whereas the bradycardic response was decreased or unchanged (7,23).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, resting bradycardia in young trained male rats has been more closely associated with alterations in cardiac pacemakers (4,5). Moreover, improvement in baroreflex control of HR observed in trained male animals (6)(7)(8) and humans (9)(10)(11) may also play a role in basal HR changes. Additionally, few studies have so far analyzed the effects of exercise training on cardiopulmonary reflex, which plays a role in the homeostasis of fluid balance.…”
Section: Introductionmentioning
confidence: 96%
“…* p<0.05 -significant statistically difference as compared to SHR Control group is associated with beneficial effects on BP, neurohumoral release and autonomic activity. However, among the antihypertensive mechanisms of exercise that remain uncertain are the increased vascular bed 38 , increased sensitivity of the baroreceptors 39 , increased formation and action of antioxidants 40 and also the modulation of sympathetic and parasympathetic tone 41 .…”
Section: Discussionmentioning
confidence: 99%